Analysis of Quantitative Trait Loci for Protein Content in Soybean Seeds using Recombinant Inbred Lines - Teuku Tajuddin (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2005)
Protein content in the seed is quantitatively inherited and controlled by polygene.  The quality of seed protein content has been studied extensively, however, information on its quantity is still limited.  In order to analyze the genetic basis of these traits, recombinant inbred lines (RILs) derived from a cross between Glycine max (L.) Merrill variety Misuzudaizu and variety Moshidou Gong 503 were planted in two environments and evaluated for seed protein content.  The broad sense heritability of the traits ranged from 0.74 to 0.79 in our RIL population.  Single-factor analysis of variance, interval mapping and composite interval mapping were used to detect significant associations between traits and genetic markers.  A total of 10 QTLs, which were significant in at least one environment were identified.  Each QTL explained the total phenotypic variation for protein content in the range from 3.4% to 29.7%.  Among all the detected QTLs, three of them were detected in both environments.  QTLs identified in this study were mapped in the soybean linkage map.  The results obtained in our study may serve as a base for analyzing the genetic control of protein content and may eventually enable to change the seed constituents.   Key words: Glycine max (L.) Merrill, quantitative trait loci, protein, recombinant inbred lines.